2010
DOI: 10.1002/mrm.22591
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of MR compatibility of a PET insert developed for simultaneous multiparametric PET/MR imaging on an animal system operating at 7 T

Abstract: The combination of positron emission tomography and MR in one system is currently emerging and opens up new domains in the functional examinations of living systems. This article reports on relevant influences of a positron emission tomography insert on MR imaging. The basic conditions of main magnetic field and RF field homogeneity were measured as well as image quality and signal-to-noise ratio when applying the usual MR sequence types including echo-planar techniques. Moreover, the influence of the positron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 19 publications
5
47
0
1
Order By: Relevance
“…To assess the influence of the PET insert on MR measurement, a uniform corn oil (which has good chemical and thermal stability and appropriate T1, T2, and proton density values that are within the biological range) phantom with T1 and T2 relaxation times of 423 and 130 ms, respectively, was scanned. Main magnetic field (B0) stability, image quality, and temporal stability of image intensity were evaluated following similar procedures used in Wehrl et al and Hong et al (23,24). Great care was taken to ensure that the relative positions of the phantom, radiofrequency coil, and main magnet were not changed during the comparative assessment.…”
Section: Assessment Of Mutual Interference Between Pet and Mrimentioning
confidence: 99%
“…To assess the influence of the PET insert on MR measurement, a uniform corn oil (which has good chemical and thermal stability and appropriate T1, T2, and proton density values that are within the biological range) phantom with T1 and T2 relaxation times of 423 and 130 ms, respectively, was scanned. Main magnetic field (B0) stability, image quality, and temporal stability of image intensity were evaluated following similar procedures used in Wehrl et al and Hong et al (23,24). Great care was taken to ensure that the relative positions of the phantom, radiofrequency coil, and main magnet were not changed during the comparative assessment.…”
Section: Assessment Of Mutual Interference Between Pet and Mrimentioning
confidence: 99%
“…Preclinical PET/MR imaging hardware for small-animal studies has advanced (2)(3)(4)12,22,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Although most preclinical PET/MR imaging systems are designed for imaging mice, there is significant interest in cardiac research using rats, especially the spontaneously hypertensive rat model of hypertensive left ventricle hypertrophy.…”
Section: Cardiac Pet/mr Imaging Current State Of Cardiac Pet/mr Imagingmentioning
confidence: 99%
“…However, technology development for rat imaging has been more challenging. To overcome these challenges, a novel imaging system has been designed at the University of Tuebingen (3,4,27,35). This system offers potential for further cardiac research in preclinical studies.…”
Section: Cardiac Pet/mr Imaging Current State Of Cardiac Pet/mr Imagingmentioning
confidence: 99%
“…A distorted magnetic field can decrease the MR image quality, especially for sequences that particularly rely on field uniformity, such as MR spectroscopy and echo planar imaging. However, several studies have shown that with sufficient shimming, the presence of additional PET hardware does not significantly affect the magnetic field homogeneity (8,9,30).…”
Section: Mrmentioning
confidence: 99%
“…The homogeneity of the radiofrequency field could be influenced by the additional PET components, affecting the flip angle. Only very small radiofrequency field map differences have been reported in preclinical (30) and clinical (8) insert-based PET/MR systems.…”
Section: Mrmentioning
confidence: 99%